Mengenal Ilmu Tadabur Al-Qur'an : (Teori dan Praktek) - Cecep Supriadi (ZAD Al-Mufassirin, 2022)
This study aims to identify tadabur as a methodology in studying the Qur'an to reveal the wisdom and instructions contained in it. In order to be able to answer contemporary challenges and problems of life. This research is classified as library research with qualitative descriptive analysis techniques, by collecting data or materials related to the discussion themes studied from library sources. The results of this study indicate that tadabur with its various approaches can reveal the wisdom and guidance of the Qur'an, more easily done by anyone who has a strong motivation to interact with it. It is different with the interpretation which has strict conditions to become a commentator, tadabur does not have any conditions except to prepare oneself physically and mentally to dive into the sea of ​​​​the Qur'an.